Tolerance to ridiculous impacts in school children with a great range of psychological well-being - Khomenko, Olena; Kofan, Iryna (Journal of Education, Health and Sport, 2023)
The impact of the psychological well-being level of high school seniors on their tolerance for cognitive load was analyzed. The study involved 93 students: 45 males and 48 females – 11th-grade students from Dnipro (Ukraine), who were categorized into three groups based on their level of psychological well-being: I – individuals with a high level of psychological well-being, II – individuals with an average level of psychological well-being, and III – individuals with a low level of psychological well-being. To determine the level of psychological well-being, the "Scales of Psychological Well-Being" (SPWB) questionnaire was used, adapted by T.D. Shevelenkova and P.P. Fesenko. Cognitive load was assessed using the correction test by V.Ya. Anfimov and arithmetic tasks, allowing the evaluation of the ability to perceive significant information. Task performance efficiency was determined by the number of correctly solved tasks in 5 minutes (accuracy) and the total number of tasks completed (speed of execution). The level of tolerance to cognitive load was assessed using E.P. Il'in's tapping test modified by G.V. Okhromiy. Tolerance to cognitive load was evaluated based on the difference in the lability of the nervous system before and after the test. Statistical processing was conducted using the Statistica 6.0 application program for Windows. It was found that students with average and high levels of psychological well-being demonstrated better tolerance to cognitive load than students with a low level of psychological well-being. At a low level of psychological well-being, males exhibited a moderate-low type of nervous system and average lability of nervous system processes, while females showed a weak type of nervous system and low lability of nervous system processes.